UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BIJI MARKISA UNGU (Passiflora edulis Sims) TERHADAP Propionibacterium acnes: ANTIBACTERIAL ACTIVITY TEST OF ETHANOL EXTRACT OF PURPLE PASSION FRUIT SEEDS (Passiflora edulis Sims) AGAINST Propionibacterium acnes - Rifani, Inesta; Ariastuti, Reni; Qonitah, Fadilah (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2025)
Inflammation of the hair follicles and sebaceous glands causes acne, a common skin disorder often triggered by bacterial infections such as Propionibacterium acnes. This study aims to determine the antibacterial activity of an ethanolic extract of purple passion fruit seeds against Propionibacterium acnes. The extraction process was carried out by maceration using 96% ethanol. The antibacterial activity of the extract was tested using the disk diffusion method (Kirby-Bauer) at concentrations of 10%, 20%, and 30%, with positive control (clindamycin) and negative control (1% DMSO) for comparison. Antibacterial activity was measured based on the inhibition zone diameter. The data obtained were then statistically analyzed using a one-way ANOVA test with a 95% confidence level. The extract yield was 5.78% and contained chemical compounds such as flavonoids, alkaloids, tannins, saponins, and terpenoids. The antibacterial test results showed inhibition zones for the 10%, 20%, and 30% extract concentrations and the positive control (clindamycin) of (6.45 ± 1.86) mm (moderate activity), (10.38 ± 0.29) mm (strong activity), (12.21 ± 1.21) mm (strong activity), and (17.78 ± 0.55) mm, respectively. Statistically, there was a significant difference in antibacterial activity between the samples (p-value < 0.05). In conclusion, the ethanolic extract of passion fruit seeds possesses antibacterial properties effective against Propionibacterium acnes.. Keywords: antibacterial, seed, Passiflora edulis Sims, Kirby_bauer, acne